2013
DOI: 10.3390/catal3040922
|View full text |Cite
|
Sign up to set email alerts
|

Rate Parameter Distributions for Isobutane Dehydrogenation and Isobutene Dimerization and Desorption over HZSM-5

Abstract: Deconvolution of the evolved isobutene data obtained from temperature-programmed, low-pressure steady-state conversion of isobutane over HZSM-5 has yielded apparent activation energies for isobutane dehydrogenation, isobutene dimerization and desorption. Intrinsic activation energies and associated isobutane collision frequencies are also estimated. A combination of wavelet shrinkage denoising, followed by time-varying flexible least squares of the evolved mass-spectral abundance data over the temperature rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…PERSPECTIVE ON POTENTIAL ZEOLITE TOPOLOGIES FOR DIMERIZATION Dimerization of isobutylene to isooctene over various zeolites as catalysts was previously reported by several researchers as presented in Table 5 and Table S4. Brown et al 227 studied dimerization of isobutylene using wavelet shrinkage denoising combined with time-varying flexible least-squares over ZSM-5 zeolite with Si/Al in the range of 16 to 17 in a reactor at 100 °C for 2 h. The activation energy of dimerization of isobutylene was 48.3 kJ/mol to 267 kJ/mol with an average activation energy of 112 kJ/mol. 227 Koskinen et al 228 reported isooctene synthesis using CO 2 and propane as solvents in reaction medium over ZSM-5 and ZSM-23 zeolites as catalysts at 100 °C and 49−89 atm for 120−200 h. The ZSM-5 catalyst with a Si/Al ratio of 23.8 had a total acidity of 380 μmol/g and the ZSM-23 catalyst with a Si/ Al ratio of 19.7 had a total acidity of 690 μmol/g.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…PERSPECTIVE ON POTENTIAL ZEOLITE TOPOLOGIES FOR DIMERIZATION Dimerization of isobutylene to isooctene over various zeolites as catalysts was previously reported by several researchers as presented in Table 5 and Table S4. Brown et al 227 studied dimerization of isobutylene using wavelet shrinkage denoising combined with time-varying flexible least-squares over ZSM-5 zeolite with Si/Al in the range of 16 to 17 in a reactor at 100 °C for 2 h. The activation energy of dimerization of isobutylene was 48.3 kJ/mol to 267 kJ/mol with an average activation energy of 112 kJ/mol. 227 Koskinen et al 228 reported isooctene synthesis using CO 2 and propane as solvents in reaction medium over ZSM-5 and ZSM-23 zeolites as catalysts at 100 °C and 49−89 atm for 120−200 h. The ZSM-5 catalyst with a Si/Al ratio of 23.8 had a total acidity of 380 μmol/g and the ZSM-23 catalyst with a Si/ Al ratio of 19.7 had a total acidity of 690 μmol/g.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Dimerization of isobutylene to isooctene over various zeolites as catalysts was previously reported by several researchers as presented in Table and Table S4. Brown et al . studied dimerization of isobutylene using wavelet shrinkage denoising combined with time-varying flexible least-squares over ZSM-5 zeolite with Si/Al in the range of 16 to 17 in a reactor at 100 °C for 2 h. The activation energy of dimerization of isobutylene was 48.3 kJ/mol to 267 kJ/mol with an average activation energy of 112 kJ/mol …”
Section: Perspective On Potential Zeolite Topologies For Dimerizationmentioning
confidence: 99%
“…The pressure-varying parameters, n ∞, P and K P , in eq are determined using methodology developed by Kalaba and Tesfatsion, called flexible least squares for time-varying linear regression (FLS-PVLR, for the analogous pressure-varying regression) and have been applied to time-varying parameters for econometric processes as well as rate constants for gas–solid reactions. For all of these processes, modeled parameters evolve slowly and smoothly over time. For isothermal adsorption, the parameters are assumed to vary slowly and smoothly with increasing pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Rate coefficients for selective oxidation can be simplified to Equation (12) where the rate coefficient ratio of activated complex to surface diffusion away from active sites control the temperature-dependence [21].…”
Section: Calculating Time-and Temperature-varying Activation Energiesmentioning
confidence: 99%
“…This compensation effect highlights the challenge in determining the true activation energies and prefactors. Rate coefficients for selective oxidation can be simplified to Equation (12) where the rate coefficient ratio of activated complex to surface diffusion away from active sites control the temperature-dependence [21].…”
Section: High-temperature Average Rate-parameters For Methacrolein Fmentioning
confidence: 99%